HIV Treatment and Prevention Report Using Cascade Analysis in Makwanpur District, Nepal, During the COVID-19 Pandemic: A Retrospective Cohort Study (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2024)
Introduction: HIV remains a significant public health concern in Nepal, emphasizing the need for effective prevention and treatment strategies. This report provides an overview of HIV treatment and prevention efforts in Nepal, evaluated through cascade analysis.Methodology: This study analysed HIV prevention and treatment activities implemented by General Welfare Pratisthan in Makwanpur district, Nepal, from January to December 2021. Hotspot mapping identified key locations for interventions targeting female sex workers (FSWs) and priority populations (PPs), including clients of FSWs and other high-risk individuals. Cascade analysis was used to assess the progression of HIV care, including outreach, HIV testing, diagnosis, antiretroviral therapy (ART) enrolment, and viral load suppression.Results: A total of 333 FSWs and 230 PPs were reached, surpassing the annual targets of 274 by 121% and 228 by 101%, respectively. HIV testing and counselling services were provided to 107 FSWs and 109 PPs, achieving 56% and 68% of the annual targets of 192 and 160, respectively. Individuals who tested positive were promptly enrolled in ART, and the number of those receiving viral load testing and achieving viral suppression also surpassed the targets, demonstrating program effectiveness.Conclusion: The findings highlight the successful implementation of HIV prevention and treatment activities in Makwanpur, despite the challenges posed by the COVID-19. Cascade analysis proved valuable for tracking progress through the HIV care continuum, offering insights into interventions effectiveness. The continued use of cascade analysis is recommended to strengthen HIV care and prevention efforts in similar settings.